2017
DOI: 10.1002/glia.23236
|View full text |Cite
|
Sign up to set email alerts
|

Ulk4 deficiency leads to hypomyelination in mice

Abstract: Brain nerve fibers are insulated by myelin which is produced by oligodendrocytes. Defects in myelination are increasingly recognized as a common pathology underlying neuropsychiatric and neurodevelopmental disorders, which are associated with deletions of the Unc-51-like kinase 4 (ULK4) gene. Key transcription factors have been identified for oligodendrogenesis, but little is known about their associated regulators. Here we report that Ulk4 acts as a key regulator of myelination. Myelination is reduced by half… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 88 publications
(132 reference statements)
0
25
0
Order By: Relevance
“…55 ULK4 belongs to the family of serinethreonine protein kinases, a group of phosphorylating kinases involved in diverse processes including cell proliferation and differ entiation, apoptosis, and embryonic development. Its deficiency leads to hypomyelination, 56 and it has been associated with neuropsychiatric traits. 57 Finally, we report a novel association on chromosome 18, located between ZBTB14, encoding a zinc finger transcription factor (zinc finger and BTB domaincontaining protein 14), and EPB41L3, encoding for a membrane protein that inhibits cell proliferation and promotes apoptosis (erythrocyte mem brane protein band 4•1like 3).…”
Section: Discussionmentioning
confidence: 99%
“…55 ULK4 belongs to the family of serinethreonine protein kinases, a group of phosphorylating kinases involved in diverse processes including cell proliferation and differ entiation, apoptosis, and embryonic development. Its deficiency leads to hypomyelination, 56 and it has been associated with neuropsychiatric traits. 57 Finally, we report a novel association on chromosome 18, located between ZBTB14, encoding a zinc finger transcription factor (zinc finger and BTB domaincontaining protein 14), and EPB41L3, encoding for a membrane protein that inhibits cell proliferation and promotes apoptosis (erythrocyte mem brane protein band 4•1like 3).…”
Section: Discussionmentioning
confidence: 99%
“…RNASeq was performed by BGI as described previously [5457] on day 100 cortical neurons from six control iPSC lines of four donors and four NRXN1α +/− lines of three patients. Transcripts were aligned to GRCH37/hg19, and abundance quantified from the FASTQ in Kallisto (v0.43.1) and presented as transcripts per million (TPM).…”
Section: Methodsmentioning
confidence: 99%
“…Ciliary disorders may be isolated or syndromic, and common features are cystic liver and/or kidney disease, blindness, neural tube defects, brain anomalies and intellectual disability, skeletal abnormalities ranging from polydactyly to abnormally short ribs and limbs, ectodermal defects, obesity, situs inversus, infertility, and recurrent respiratory tract infections [Oud et al, 2017]. Liu et al [2017Liu et al [ , 2018b, demonstrated that ULK4 is also a crucial regulator of myelination. Moreover, Liu et al [2018 a ] have shown for the first time that Ulk4 haploinsufficiency in mice leads to increased anxiety-related behavior with disturbed GABAergic signaling.…”
Section: Discussionmentioning
confidence: 99%